The use of ethnography to explore tourist satisfaction antecedents - Christou, Prokopis A.; Saveriades, Alexis (My University, 2010)
The purpose of this paper is to provide insights concerning the use of ethnographic techniques to explore the antecedents of tourist satisfaction, otherwise referred to as the needs and expectations which precede tourist satisfaction. By revealing the relevance of both needs and expectations in the tourist satisfaction process, the authors proceed in justifying the use of this approach for such exploration. This is based on a thorough review of the global literature as well as on a prolonged ethnographic study undertaken in Cyprus which aimed to investigate holistically the rural tourist satisfaction process. Based on the results of the study, the authors encourage future researchers in the respective tourism field to adopt and make use of the aforementioned approach for similar investigations. University of the Aegean. Printed in Greece.
Keywords: Ethnography; Tourist satisfaction; Antecedents; Needs; Expectations